Effect of Maturation on Hemodynamic and Autonomic Control Recovery Following Maximal Running Exercise in Highly Trained Young Soccer Players - Buchheit, Martin; Al Haddad, Hani; Mendez-Villanueva, Alberto; Quod, Marc J.; Bourdon, Pitre C. (Frontiers in Physiology, 2011)
The purpose of this study was to examine the effect of maturation on post-exercise hemodynamic and autonomic responses. Fifty-five highly-trained young male soccer players (12-18 yr) classified as pre-, circum- or post-peak height velocity (PHV) performed a graded running test to exhaustion on a treadmill. Before (Pre) and after (5th-10th min, Post) exercise, heart rate (HR), stroke volume (SV), cardiac ouput (CO), arterial pressure (AP) and total peripheral resistance (TPR) were monitored. Parasympathetic (high-frequency [HFRR] of HR variability (HRV) and baroreflex sensitivity [Ln BRS]) and sympathetic activity (low-frequency [LFSAP] of systolic AP variability) were estimated. Post-exercise blood lactate [La]b, the HR recovery (HRR) time constant and parasympathetic reactivation (time varying HRV analysis) were assessed. In all three groups, exercise resulted in increased HR, CO, AP and LFSAP (P<0.001), decreased SV, HFRR and Ln BRS (all P<0.001), and no change in TPRI (P=0.98). There was no ‘maturation x time’ interaction for any of the hemodynamic or autonomic variables (all P>0.22). After exercise, pre-PHV players displayed lower SV, CO and [La]b, faster HRR and greater parasympathetic reactivation compared with circum- and post-PHV players. Multiple regression analysis showed that lean muscle mass, [La]b and Pre parasympathetic activity were the strongest predictors of HRR (r2=0.62, P<0.001). While pre-PHV players displayed a faster HRR and greater post-exercise parasympathetic reactivation, maturation had little influence on the hemodynamic and autonomic responses following maximal running exercise. HRR relates to lean muscle mass, blood acidosis and intrinsic parasympathetic function, with less evident impact of post-exercise autonomic function.